Prevalence of Scabies and Impetigo 3 Years After Mass Drug Administration With Ivermectin and Azithromycin. (25th May 2019) - Marks, Michael; Romani, Lucia; Sokana, Oliver; Neko, Lazarus; Harrington, Relmah; Nasi, Titus; Wand, Handan; Whitfeld, Margot J; Engelman, Daniel; Solomon, Anthony W; Kaldor, John M; Steer, Andrew C
Abstract: Background: Ivermectin-based mass drug administration has emerged as a promising strategy for the control of scabies and impetigo in settings where the diseases are endemic. Current follow-up data are limited to 12 months for the majority of studies. Longer-term data are vital to inform the sustainability of interventions. Methods: We conducted a prevalence survey for scabies and impetigo in 10 villages in Choiseul Province of the Solomon Islands 36 months after a single round of ivermectin and azithromycin mass drug coadministration. In the primary analysis, we compared the prevalence of scabies and impetigo at 36 months to the prevalence at baseline. Results: At 36 months, the prevalence of scabies was 4.7% (95% confidence interval [CI], 3.6–6.1), which was significantly lower than at baseline (18.7%; relative reduction, 74.9%; 95% CI, 61.5%–87.7%; P < .001). The prevalence of impetigo was 9.6% (95% CI, 8.1%–11.4%), significantly lower than at baseline (24.7%; relative reduction, 61.3%; 95% CI, 38.7%–100%; P < .001). The highest prevalence of scabies was among children aged <5 years (12.5%; adjusted odds ratio, 33.2; 95% CI, 6.6–603.2), and the highest prevalence of impetigo was among children aged 5–9 years (16.4%; adjusted odds ratio, 8.1; 95% CI, 3.6–21.8). Conclusions: There was a sustained impact of a single round of ivermectin and azithromycin mass drug coadministration on the prevalence of scabies and impetigo 3 years after the intervention. Our data provide further support to adopt this intervention as a central component of global scabies control efforts. Clinical Trials Registration: Australian and New Zealand Trials Registry (ACTRN12615001199505). Abstract : Ivermectin-based mass drug administration is a promising strategy for scabies. Most studies only report 12-month outcomes. We demonstrate that the prevalence of scabies and impetigo remain low 3 years after large-scale intervention in the Solomon Islands.